A influência da manutenção no desempenho térmico de um trocador de calor de placas - Gaidex, Carlos Daniel (2019)
This Work Course Conclusion had the objective analyzing the effect of the maintenance on the plate heat exchanger and verifying its performance by comparing the heat transfer. The methodology used in the quantification of the heat transfer is through the Energy Balance and Effectiveness-NTU (Number of Transfer Unit). To perform the maintenance in the heat exchanger was used the NBR 13971: 2014 and information contained in catalogs, for the experimental tests. Regarding the objectives of the research, the experiment integrates the assimilation of the problematic with bibliographic studies for complementation, being considered an exploratory research. The study was conducted in the Didactic Laboratory of Thermal Sciences of the Academic Department of Mechanics of UTFPR / Campus Ponta Grossa. The tests performed on the plate heat exchanger were in countercurrent flow, with three variations in the flow of the hot fluid, three variations in the flow of the cold fluid and four variations in the temperature of the reservoir. The result was the increase in heat transfer in both methods applied for the calculation, with an overall average increase of 5.1%, proving the effect of non-programmed corrective maintenance.